Peran pembangunan ekonomi daerah terhadap peningkatan kinerja ekonomi dikabupaten probolinggo - Lailiya Dwi Maghfirah; Sinta Nuriah Kamilah; Deddy Junaedi (PT. Saha Kreasi Indonesia, 2026)
Regional economic development is a strategic instrument for enhancing economic performance and achieving sustainable community welfare. This study aims to analyze the role of regional economic development in improving the economic performance of Probolinggo Regency. A descriptive qualitative approach with a literature review method was employed. Data were collected from economic development textbooks, national and international journal articles, and official publications of the Probolinggo Regency Central Bureau of Statistics. Data analysis was conducted using descriptive qualitative techniques through the classification, comparison, and synthesis of relevant findings from the literature. The findings indicate that regional economic development contributes significantly to improving the economic performance of Probolinggo Regency, as reflected in the growth of Gross Regional Domestic Product (GRDP) and the improvement of the Human Development Index (HDI). The regional economic structure, which is still dominated by the agricultural sector, highlights the importance of strengthening leading sectors based on local potential through value-added enhancement and technological innovation. However, the high dependence on the primary sector increases economic vulnerability, necessitating economic diversification through the development of secondary and tertiary sectors, particularly manufacturing industries and micro, small, and medium enterprises (MSMEs). The role of local government as a regulator, facilitator, and catalyst is identified as a key determinant in promoting inclusive and sustainable regional economic growth.